LuQi Formula Regulates NLRP3 Inflammasome to Relieve Myocardial-Infarction-Induced Cardiac Remodeling in Mice. (28th June 2021) - Zhang, Xiaoqing; Zhao, Dandan; Feng, Jiling; Yang, Xiaoli; Lan, Zhenzhen; Yang, Tao; Kong, Xiaoni; Qu, Huiyan; Zhou, Hua
Abstract : Background . Excessive activation of the nod-like receptor family pyrin domain containing 3(NLRP3) inflammasome plays a significant role in the progression of cardiac injury. In China, it has been well recognized that Chinese herbal medicine is markedly effective in treating cardiovascular diseases (CVDs). LuQi Formula (LQF) has been used clinically for more than 10 years and confirmed to be effective in improving cardiac function and inhibiting apoptosis. However, the specific mechanisms underlying its efficacy are mostly unknown. This study aimed to evaluate whether LQF could alleviate cardiac injury and apoptosis by regulating the NLRP3 inflammasome and the caspase-3/Bax pathway. Purpose . In this study, we investigated the effects of LQF on cardiac remodeling in a mouse model of myocardial infarction (MI) in vivo. Methods . Forty male C57BL/6 mice were randomly divided into four groups: the sham group, the model group, the LQF group, and the perindopril group, with a sample size ( n ) of 10 mice in each group. Except the sham group, the other groups received left anterior descending (LAD) coronary artery ligation to induce MI and then treated with LQF, perindopril, or saline. Six weeks after MI, echocardiography was used to evaluate cardiac structure and function. Myocardial tissue morphology was observed by haematoxylin and eosin (H&E) staining, and heart samples were stained with Masson's trichrome to analyse myocardial fibrosis. Myocardial hypertrophy was observed by fluorescent wheat germ agglutinin (WGA) staining. The expressions of NLRP3, ASC, Cle-caspase-1, IL-1 β, TXNIP, Cle-caspase-3, Bcl-2, and Bax in heart tissues were assessed by western blot analysis. mRNA expressions of ANP and BNP in heart tissues were measured by RT-PCR. The expression of reactive oxygen species in myocardial tissue was detected by using a DCFH-DA probe. Results . Echocardiographic analysis showed that compared with the model group, the left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) in the LQF and perindopril group were increased (P < 0.05 ), left ventricular internal diameter end diastole (LVIDd) and left ventricular internal diameter end-systole (LVIDs) were reduced (P < 0.05 ), and H&E and Masson's trichrome staining of cardiac tissues showed that LQF and perindopril could partially reverse ventricular remodeling and alleviate myocardial fibrosis (P < 0.05 ). WGA fluorescence results showed that compared with the model group, myocardial hypertrophy was significantly reduced in the LQF and perindopril group. We also found that LQF and perindopril reduce the oxidative stress response in the heart of MI mice. The protein expression of NLRP3, ASC, Cle-caspase-1, IL-1 β, TXNIP, Cle-caspase-3, and Bax was downregulated in the LHF and perindopril treatment group, and Bcl-2 expression was upregulated. Conclusion . LQF and perindopril significantly attenuated cardiac injury and apoptosis in the MI model. In addition, we found that LQF effectively inhibited the activation of the NLRP3/ASC/caspase-1/IL-1 β cascade, decreased inflammatory infiltration, delayed ventricular remodeling, and downregulated caspase-3/Bax signaling, which can effectively reduce the apoptosis of cardiomyocytes. Perindopril showed the same mechanism.